2022
DOI: 10.3389/fcvm.2022.1013426
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Percutaneous adrenal arterial embolization cures resistant hypertension

Abstract: BackgroundPrimary aldosteronism is a common cause of resistant hypertension. Patients with primary aldosteronism due to aldosterone-producing adenoma are generally treated with unilateral adrenalectomy or medical therapy. Superselective adrenal arterial embolization is an alternative treatment for patients with unilateral primary aldosteronism.Case summaryWe present a 39-year-old male patient with a 5-year history of primary aldosteronism and secondary hypertension. The patient refused adrenalectomy while acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The technique can be technically challenging with limited control of the ethanol distribution profile, and as such its application has been limited. However, it does provide an alternative option for patients who refuse surgery or in those for whom surgery is considered high risk ( 201 ). In a recent prospective, medication-controlled study, the authors observed complete or partial hypertension remission as well as biochemical improvement in most patients following catheter-based adrenal ablation at a comparable level to those undergoing adrenalectomy.…”
Section: Novel Treatment Approachesmentioning
confidence: 99%
“…The technique can be technically challenging with limited control of the ethanol distribution profile, and as such its application has been limited. However, it does provide an alternative option for patients who refuse surgery or in those for whom surgery is considered high risk ( 201 ). In a recent prospective, medication-controlled study, the authors observed complete or partial hypertension remission as well as biochemical improvement in most patients following catheter-based adrenal ablation at a comparable level to those undergoing adrenalectomy.…”
Section: Novel Treatment Approachesmentioning
confidence: 99%